2021
DOI: 10.1016/j.yebeh.2021.107771
|View full text |Cite
|
Sign up to set email alerts
|

Cognition in adult patients with newly diagnosed non-lesional temporal lobe epilepsy

Abstract: Objective: To evaluate whether cognitive performance is affected in newly diagnosed temporal lobe epilepsy (TLE) and to determine the most vulnerable cognitive domains. Methods: In this baseline longitudinal study, differences in memory and non-memory cognitive functions were assessed using comprehensive neuropsychological test batteries in 21 adult patients with newly diagnosed non-lesional TLE and individually matched controls. In addition, the analyses included ratings of self-perceived emotional status. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 49 publications
(78 reference statements)
2
16
0
Order By: Relevance
“…In a previous study, we recently found slight cognitive deficits at the time of diagnosis in the same cohort of patients as utilized in the present study ( 26 ). Reduced scores on some of the executive function tests led us to suspect that extratemporal or network dysfunction might be present at an early stage.…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations
“…In a previous study, we recently found slight cognitive deficits at the time of diagnosis in the same cohort of patients as utilized in the present study ( 26 ). Reduced scores on some of the executive function tests led us to suspect that extratemporal or network dysfunction might be present at an early stage.…”
Section: Introductionsupporting
confidence: 70%
“… * Four patients and one control subject have several abnormalities. For details of these mainly clinically insignificant findings, see Bjørke et al ( 26 ) for details . ** Four patients have both nonspecific and epileptiform abnormalities .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using only these patients, however, makes it difficult to determine how memory naturally deteriorates as the disease progresses. Bjørke et al (2021) 12 evaluated cognition in patients newly diagnosed with TLE and found that these patients often display cognitive deficits, despite the absence of structural brain abnormalities in some patients. These findings support the association of memory impairment to an underlying pathology.…”
Section: Epilepsy and Memory Impairmentsmentioning
confidence: 99%